Teaching and learning mathematics with problem solving approach: Learning activities and instructional practice - Noura, Karim; Pradana, Kenny Candra; Syazali, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examined the implementation of problem-solving-based learning in mathematics education within schools in Victoria, Australia. It aimed to evaluate its effectiveness in enhancing students' critical, logical, and creative thinking skills while identifying challenges in integrating this approach into the curriculum. A qualitative descriptive method was employed, involving literature review, classroom observations, and informal interviews with teachers and students. Data collection focused on exploring instructional practices and their alignment with curriculum objectives. Results indicated that problem-solving activities fostered conceptual understanding and practical application of mathematics in real-life scenarios. Examples, such as measuring distances using average steps and solving optimization problems, demonstrated increased student engagement and comprehension of mathematical concepts. However, challenges included teachers' limited understanding of problem-solving strategies, insufficient resources, and language barriers in interpreting real-world problems. Despite these obstacles, integrating structured activities and diverse instructional strategies proved to be a promising method for improving mathematical learning outcomes. These findings underscore the importance of aligning pedagogical practices with curriculum goals to enhance mathematics education.